Jiyuan oridonin A induces differentiation of acute myeloid leukemia cells including leukemic stem-like cells - Li, Fahui; Gao, Congying; Li, Xueming; Wang, Jiangyun; Zhao, Yao; Ke, Yu; Liu, Ying; Liu, Hong-Min; Hu, Zhenbo; Wei, Liuya; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
Acute myeloid leukemia (AML) is an aggressive hematological neoplasia characterized by failure of myeloid differentiation. AML is a leading cause of death from leukemia. Cytarabine chemotherapy resistance is a major source of refractory/relapsed AML. A major obstacle to the successful treatment of AML results from residual disease maintained by leukemic stem cells (LSCs), which are mostly resistant to conventional chemotherapy. Here, we determined the effect of a natural compound, Jiyuan oridonin A (JOA), on the differentiation blockade in M2 subtype [particularly t(8;21)] of AML cells, M3 subtype of AML cells (APL cells) and leukemic stem-like cells both in vitro and in vivo. We found that JOA induced cell differentiation and suppressed the colony formation capacity in various AML cell lines (Kasumi-1, KG-1, MUTZ-8, NB4 and HL-60) without eliciting apoptosis. The mechanism of JOA-induced cell differentiation depends on the specificity of cell type. JOA mediated the differentiation of Kasumi-1 cells by activating the hematopoietic cell lineage signaling pathway, while inhibition of c-MYC was involved in the JOA-induced differentiation of NB4 cells. Moreover, JOA was identified to target leukemic stem-like cells by induced cell differentiation in vivo. These findings demonstrated that JOA could inhibit the proliferation of M2, M3 subtype of AML cells and leukemic stem-like cells by overcoming the differentiation blockade, which offers a novel therapeutic strategy for AML to overcome relapse and drug resistance in patients with AML. Our findings highlight the possibility of using compounds like JOA as a promising differentiation-induced agent for the treatment of AML.